A Genetic Variant rs1020760at NFKB1 is Associated with Clinical Features of Psoriasis Vulgaris in a Han Chinese Population. (July 2016) - Wang, Wenjun; Zhu, Zhengwei; Zhu, Caihong; Zheng, Xiaodong; Zuo, Xianbo; Chen, Gang; Zhou, Fusheng; Liang, Bo; Tang, Huayang; Wang, Zaixing; Zhang, Xuejun; Sun, Liangdan
Summary: Psoriasis vulgaris is a chronic inflammatory skin disease associated with complex genetic susceptibility. Recently, we identified a single‐nucleotide variant rs1020760 at NFKB1 significantly associated with psoriasis in a Han Chinese population in deep analysis of exome and targeted sequencing ( P = 1.76 × 10 −8 ). To investigate the potential association between rs1020760 and phenotypes of psoriasis vulgaris, we performed a genotype–phenotype analysis. A total of 9946 cases and 9906 controls with detailed clinical and demographic information were involved in this study, while the genotype data of rs1020760 was available in the previous targeted sequencing study of psoriasis. Genotype‐based association testing revealed the additive model might provide the best fit for rs1020760 ( P = 5.44 × 10 −8 ). Case‐only analysis showed that the distribution of allele G was significantly different between the cases with and without family history ( P allele = 4.07 × 10 −3, P genotype = 5.75 × 10 −3 ). The differences in allele and genotype frequencies were observed between all the subphenotypes and controls except for the genotype frequency of the late onset subgroup, while no difference was found in case‐only analysis for the other two subphenotypes. Rs1020760 was preferentially associated with family history of psoriasis, implying that NFKB1 might not only play important roles in the development of psoriasis, but might also contribute to the special phenotypes of this disease.